Stepwise nitrosylation of the nonheme iron site in an engineered azurin and a molecular basis for nitric oxide signaling mediated by nonheme iron proteins. Issue 19 (16th April 2021) - Tian, Shiliang; Fan, Ruixi; Albert, Therese; Khade, Rahul L.; Dai, Huiguang; Harnden, Kevin A.; Hosseinzadeh, Parisa; Liu, Jing; Nilges, Mark J.; Zhang, Yong; Moënne-Loccoz, Pierre; Guo, Yisong; et al.
Abstract : Stepwise nitrosylation from Fe(ii ) to FeNO 7, FeNO 8 and then to {Fe(NO)2 } 9 is reported for the first time in the same protein scaffold, providing deeper understanding of the detailed mechanism of dinitrosyl iron complex formation. Abstract : Mononitrosyl and dinitrosyl iron species, such as FeNO 7, FeNO 8 and {Fe(NO)2 } 9, have been proposed to play pivotal roles in the nitrosylation processes of nonheme iron centers in biological systems. Despite their importance, it has been difficult to capture and characterize them in the same scaffold of either native enzymes or their synthetic analogs due to the distinct structural requirements of the three species, using redox reagents compatible with biomolecules under physiological conditions. Here, we report the realization of stepwise nitrosylation of a mononuclear nonheme iron site in an engineered azurin under such conditions. Through tuning the number of nitric oxide equivalents and reaction time, controlled formation of FeNO 7 and {Fe(NO)2 } 9 species was achieved, and the elusive FeNO 8 species was inferred by EPR spectroscopy and observed by Mössbauer spectroscopy, with complemental evidence for the conversion of FeNO 7 to {Fe(NO)2 } 9 species by UV-Vis, resonance Raman and FT-IR spectroscopies. The entire pathway of the nitrosylation process, Fe(ii ) → FeNO 7 → FeNO 8 → {Fe(NO)2 } 9, has been elucidated within the same protein scaffold based on spectroscopic characterization and DFT calculations. These results not only enhance the understanding of the dinitrosyl iron complex formation process, but also shed light on the physiological roles of nitric oxide signaling mediated by nonheme iron proteins.